APPLICATION OF THE SYSTEM OF BALANCED FACTORS FOR MANAGEMENT OF INNOVATION-INVESTMENT PROJECTS - Mukhammat Baichorov (Вестник Северо-Кавказского федерального университета, 2022)
The article analyses the conceptual mechanism concerning management of innovation-investment projects, characteristics of projects management and application of the system of balanced factors for management of innovation-investment projects are given.